A rare nonsyndromic presentation of bilateral doughnut shaped lip pits in an Indian child - Senthil Balasubramani; Sudhakar Sankaran; Abhishek Madhavan; Selvakumar Jayaraman (Wolters Kluwer Medknow Publications, 2016)
Lip pits are a rare congenital anomaly that presents on the upper or lower lip or the commissure of the lips. Lip pits are an autosomal dominant trait occurring almost always in association with cleft lip or palate. They most commonly occur in association with developmental disturbances such as Van der Woude's syndrome, popliteal pterygium syndrome, oro-facial-digital syndrome, Marres-Cremers syndrome, and Hirschsprung disease. Its occurrence in nonsyndromic individuals is extremely rare with only a handful of cases reported. The identification of lip pits with other associated anomalies is crucial for genetic counseling; we report a case of nonsyndromic presentation of bilateral lip pits.